Comparative Evaluation of Root Surface Changes by Air-Polishing using Glycine and Chlorhexidine Acetate Powder: An in-vitro Study - Shukla, Hardi Rajanbhai; Mathur, Aditi; Shetty, Neema; Makhijani, Barkha; Manohar, Balaji (Journal of Nepalese Society of Periodontology and Oral Implantology, 2017)
Background: Biofilm removal is the central part of the etiotropic and maintenance phase of periodontal therapy. Commercially available injection water jets such as Prophy-Jet allows an efficient and convenient biofilm removal as an adjunct to mechanical periodontal therapy. But, due to the abrasive nature of traditionally used air polishing powders such as sodium bicarbonate, there is a continuous research going on for less abrasive materials. Aims: To compare the effectiveness of air polishing using glycine powder and chlorhexidine acetate powder on tooth surface as compared to ultrasonic scaling and also to evaluate the time taken for stain removal. Materials and Methods: Thirty fully erupted, single rooted teeth extracted due to poor periodontal prognosis were used in this in-vitro study. The sample teeth were divided into 3 equal groups and stained in coffee solution. The test Groups A and B underwent air-polishing with glycine powder and chlorhexidine acetate powder respectively. Group C was control group and underwent ultrasonic scaling. Time taken for stain removal was recorded. The sample teeth were also evaluated under a stereo-microscope and digital micrometer preprocedurally and post-procedurally to measure surface changes. Results: The study showed statistically significant results (p<0.05) when measurements of changes in surface roughness of samples treated with glycine powder air-polishing were compared with ultrasonic scaling and chlorhexidine acetate powder air-polishing were compared with ultrasonic scaling. Surface texture loss as well as time taken for stain removal was minimum with glycine powder and maximum with ultrasonic scaling. Conclusion: Air-polishing with glycine powder was least abrasive on root surface followed by chlorhexidine acetate powder air-polishing. This is because of the lower particle size of glycine which also covers larger area in lesser time.